2017
DOI: 10.1038/s41598-017-17725-z
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient upconversion of Er3+ in Yb3+ codoped non-cytotoxic strontium lanthanum aluminate phosphor for low temperature sensors

Abstract: Er3+ and Er3+/Yb3+ melilite-based SrLaAl3O7 (SLA) phosphors were synthesized by a facile Pechine method. The differences in emission intensities of 4I13/2 → 4I15/2 transition in NIR region when excited with Ar+ and 980 nm lasers were explained in terms of energy transfer mechanisms. Temperature and power dependence of upconversion bands in the visible region centered at 528, 548 and 660 nm pertaining to 2H11/2, 4S3/2 and 4F9/2 → 4I15/2 transitions were investigated. Fluorescence intensity ratio (FIR) technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 53 publications
0
38
0
Order By: Relevance
“…Despite having typical restrictions, [16,17] a large number of reports validate the applicability of such coupled states as temperature sensor in diverse situations. [18][19][20][21][22][23] It is easy to visualize that devising a cryogenic (< 100 K) luminescent thermometer based on the same principle is challenging because thermal mechanism becomes extremely inefficient for delivering carriers to the higher excited state to have any meaningful luminescence [24] and thus has hardly been ventured. [25][26][27] Below certain temperatures, perhaps the primary population pathway of the higher state may also change, and the intensity ratio may not follow a rigid Boltzmann's distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Despite having typical restrictions, [16,17] a large number of reports validate the applicability of such coupled states as temperature sensor in diverse situations. [18][19][20][21][22][23] It is easy to visualize that devising a cryogenic (< 100 K) luminescent thermometer based on the same principle is challenging because thermal mechanism becomes extremely inefficient for delivering carriers to the higher excited state to have any meaningful luminescence [24] and thus has hardly been ventured. [25][26][27] Below certain temperatures, perhaps the primary population pathway of the higher state may also change, and the intensity ratio may not follow a rigid Boltzmann's distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The Er 3+ ion has suitable TCLs, which result in a good t of FIR not only for induced optical heating but also for temperature sensing of phosphor materials. [23][24][25][26][27][28] In the UC photoluminescence of Er 3+ /Yb 3+ co-doped phosphors, the Er 3+ ion weakly absorbs an incident near infrared (NIR) 980 nm photon and gives poor UC emission intensity. However, its efficiency can be enriched signicantly via the doping of Yb 3+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] A number of studies was carried out by researchers using Er 3+ /Yb 3+ ions in different phosphor materials. [23][24][25][26][27][28]50 These authors have found FIR by taking UC emission intensities of TCLs of green emission as a function of temperature. It is well known that the 2 H 11/2 and 4 S 3/2 levels of Er 3+ ion are thermally coupled and they give rise to different values of UC emission intensities as a function of external temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 As is known, the photoluminescence (PL) behaviors of the trivalent rare-earth ions are distinctly affected by the luminescent host material, especially, low phonon energy material since it can improve the possibility of the radiative transition. 16,17 To date, many inorganics, such as molybdates, silicates, ceramic, uorides and oxides, were developed as the luminescent host materials for the trivalent rare-earth ions. [18][19][20][21][22] Compared with other materials, the uorides, which exhibit a low phonon energy (<350 cm À1 ), are thought of a splendid luminescent host material for trivalent rare-earth ions.…”
Section: Introductionmentioning
confidence: 99%